2017
DOI: 10.3389/fpsyg.2017.01735
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Urban Spaces with Different Level of Restorativeness Based on the Original and on a Shorter Version of Hartig et al.’s Perceived Restorativeness Scale

Abstract: Restorativeness is defined as the potential of the environment to re-establish certain cognitive capacities related to human information processing. The most frequently used instrument for evaluating the restorativeness of places is the Perceived Restorativeness Scale, proposed by Hartig et al. (1991). Later on, shorter versions of the Perceived Restorativeness Scale were proposed. The aim of this work is to evaluate the discriminatory capacity of the original and of a shorter Spanish version of the PRS, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
1
18
0
3
Order By: Relevance
“…In addition, the results of restorativeness were not in accordance with the findings by Sonntag-Öström, et al [ 58 ], who reported that four types of green environments all scored much higher than a city environment. There was an assumption that urban environments were inherently lacking stress-reducing and mood-enhancing functions [ 18 ], and the restorative effects of urban areas were possibly associated with urban greening [ 45 ]. However, in the present study, only a few plants were observed in the urban area, and the restorativeness of the nighttime urban environment did not seem to be strongly associated with plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results of restorativeness were not in accordance with the findings by Sonntag-Öström, et al [ 58 ], who reported that four types of green environments all scored much higher than a city environment. There was an assumption that urban environments were inherently lacking stress-reducing and mood-enhancing functions [ 18 ], and the restorative effects of urban areas were possibly associated with urban greening [ 45 ]. However, in the present study, only a few plants were observed in the urban area, and the restorativeness of the nighttime urban environment did not seem to be strongly associated with plants.…”
Section: Discussionmentioning
confidence: 99%
“…A shortened version of the Perceived Restorativeness Scale (PRS) was used to measure perceived restorativeness of environment based on the Attention Restoration Theory [ 42 , 43 , 44 ]. The reliability and validity of the short scale were tested previously [ 45 ]. The scale consists of five items with a 10-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…The Restorative Capacity scale, translated into Spanish and used by Ruiz and Hernández (2014) and Negrín et al (2017) from the original scale proposed by Berto (2005), which, in turn, was developed as a reduced version of Korpela and Hartig's (1996) Perceived Restorativeness Scale (PRS), is composed of five items whose response scale is Likert type from one to five, with 1 being "Totally disagree" and 5 "Totally agree. " The internal consistency was 0.82.…”
Section: Materials and Instrumentsmentioning
confidence: 99%
“…Two prevailing theories of restorativeness in the natural environment are widely applied: attentional restoration theory (ART) (Kaplan and Kaplan, 1989;Kaplan, 1995) and stress recovery theory (SRT) (Ulrich et al, 1991). The perceived restorativeness scales (PRS) have been developed according to ART to evaluate people's recovery levels in different environments (Hartig et al, 1997;Fátima et al, 2017), which contains four main components with 16 items in total: Fascination (the attraction of involuntary, effortless attention); Being-Away (a shift away from the present daily routine to a different environment); Compatibility (fit to an individual's planned behavior and environmental demands); and Extent (it can be experienced through immersion in intellectual activities and in physical environments.) (Hartig et al, 1996(Hartig et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%